Bridging the divide - Pelizzo, Riccardo; Nwokora, Zim (Politics and Policy, 2016)
Party systems research has proceeded along two parallel lines of inquiry, one predominantly “qualitative” and the other “quantitative.” This article attempts to bridge this divide in two ways. First, by showing that qualitative information can be valuable in the construction of quantitative measures. Second, by showing that the results from applying theoretically- sensitive measurement tools can be useful for qualitative classification. These analyses are performed using an original dataset of party system changes in Sub-Saharan Africa.
Keywords: party system; Africa South of the Sahara; system change